A comparative study of production control systems through simulation - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
The purpose of this paper is to simulate pull, push and hybrid production control systems for a single line, multi-stage and continuous production process, which is aluminium casting, in order to compare their performances where the current production control system is push system. The paper also provides an approach in constructing, hybrid system by using TSP in minimizing total setup time to obtain optimal sequence of orders.
Keywords: production control systems; pull system; push system; hybrid system; simulation; PUSH